2021
DOI: 10.1002/adsu.202000269
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Intercropping Systems of Black Cumin (Nigella sativa L.) and Fenugreek (Trigonella foenum‐graecum L.) through Inoculation with Bacteria and Mycorrhizal Fungi

Abstract: This study evaluates the effects of intercropping patterns, plant growth‐promoting rhizobacteria and arbuscular mycorrhizal fungi (AMF) on seed yield and yield components of black cumin (Nigella sativa L.) and fenugreek (Trigonella foenum‐graecum L.), as well as the essential oil and fatty acid profile of black cumin. A two‐year two‐factorial field experiment was conducted in 2015 and 2016 to investigate intercropping of black cumin and fenugreek in five ratios and biofertilizer application as AMF and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Fennel and fenugreek were planted at 40 cm row spacing in 4-m long rows. The on-row spacing between plants was adjusted to 10 cm for fenugreek and 25 cm for fennel, resulting in plant densities of 25 and 10 plants m –2 , respectively 29 . Fennel and fenugreek (Urmia local landraces) seeds were obtained from the Agricultural and Natural Resources Organization of Urmia, Iran.…”
Section: Methodsmentioning
confidence: 99%
“…Fennel and fenugreek were planted at 40 cm row spacing in 4-m long rows. The on-row spacing between plants was adjusted to 10 cm for fenugreek and 25 cm for fennel, resulting in plant densities of 25 and 10 plants m –2 , respectively 29 . Fennel and fenugreek (Urmia local landraces) seeds were obtained from the Agricultural and Natural Resources Organization of Urmia, Iran.…”
Section: Methodsmentioning
confidence: 99%
“…Intercropping combines two or more plant species on the same land for a considerable proportion of their growing periods (Rezaei‐Chiyaneh, Battaglia, et al, 2021; Gitari et al, 2020). It is widely practiced for its more efficient use of environmental resources, increased nutrient uptake, reduced incidence of pathogens, weeds, and pests, improved soil fertility through N fixation by legumes, and increased crop quantity and quality (Gitari et al, 2018; Raza et al, 2019; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of a biostimulant may be related to nutrient availability, and its direct role in plants by foliar application enhances the photosynthetic activity of enzymes and precursors of EOs, counting isoprenes, and phenylpropanes (Rehman et al, 2016 ). Rezaei-Chiyaneh et al ( 2021 ) reported that biostimulant application in aromatic crops, viz ., black cumin ( Nigella sativa L.) and fenugreek ( Trigonella foenum-graecum L.), enhanced EO quantity and quality. Additionally, EO profile varies according to climate, geographical features, and date of collection (Swamy and Sinniah, 2015 ).…”
Section: Discussionmentioning
confidence: 99%